Utilization of Dissociation Constant (pKa) Value Perspective of -CH Acid in Electrochemical Synthesis of 4H-Chromene and its Derivatives - Saraswat, Apoorv; Pal Singh, Rana Krishna (Asian Journal of Chemistry, 2020)
Activation of acidic-H in C-H chemistry through imposition of proper electrode potential is a matter of concern among synthetic research community. In this study, our main aim is to get deeper insight into the dissociation constant (pKa) value perspective of -CH acid and its utilization in electro-catalytic transformation. Herein, a platinum cathode was being used to attract a covalently bonded electrons that exist between C and active-H of CH-acid (dimedone) toward itself i.e. cathodic part to form acidic-H and thus, form in-situ tautomeric enol form that acts as electro-generated base. Utilization of this notability has been accomplished by electrochemical synthesis of 4H-chromene and its derivatives by performing cathodic reduction. Due to acidic property of dimedone, cathodic platinum electrode draw the potential switched to lower side that is being recorded through the potential-cum-galvanostat which facilitates the faster transfer of electrons from -CH acid to form enolate ion of dimedone that act as electro-generated base for the reaction media which simultaneously undergoes cascade reaction (Michael addition/cyclization) on activated alkene (α-cyanocinnamonitrile derivatives). This approach offers several advantages such as good yield, mild reaction condition, easy accessible, simple work-up procedure and controlled potential selectivity at cathode. Use of no base is pivotal section of this methodology. Electro-generated base is used instead of chemical toxic bases, so the present protocol is green as electrons that acts as intrinsically sole reagent for the reaction media which is renewable, hence sustainable for the safe future.